MODEL KINERJA UKM BERBASIS PERILAKU KERJA INOVATIF DI KOTA JAMBI - Ahmad Firdaus, - (2021)
The purpose of this study is to find a model for improving SMEs performance through innovative work behavior, knowledge sharing, IT usage and organizational commitment. The research method used is descriptive verification analysis, with the object includes 5 variables namely organizational commitment (Afective Commitment, Normativ Commitment, Continuance Commitment), IT Usage, knowledge sharing, innovative work behavior and SMEs performance, while the subject used as the unit of analysis is the owner or leader of SMEs in the City of Jambi. The population in this study amounted to 4408 SMEs, while the number of analysis units was 367 SMEs in Jambi City. Data analysis using Structural Equation Modeling (SEM) data processing through Amos v.22 software. The results of this study prove that the level of organizational commitment can affect the level of SMEs performance, the level of knowledge sharing can mediate the influence of the level of organizational commitment and IT Usage to the level of SMEs performance, the level of innovative work behavior can mediate the effect of the level of organizational commitment and IT Usage to the level of SMEs performance, the level of innovative work behavior can mediate the effect of the level of knowledge sharing on the level of SMEs performance. Novelty in this study is found a model of SMEs performance improvement strategies that involve innovative work behavior, knowledge sharing, IT usage and organizational commitment.